Mechanical Properties of Polymeric Composite Based on Pine Seeds Production Residues - Kolář, Viktor; Tichý, Martin; Müller, Miroslav (Manufacturing Technology Journal, 2019)
An aim of the research is mechanical properties evaluation of the polymeric particulate composite based on the pine seeds production residues, i.e. the pinecones. Current trends in composite materials field are a substitution of synthetic fillers by biological fillers. An adhesive modification by biological fillers can improve its mechanical properties and reduce cost, which reduces total costs for composite system production. The polymeric adhesive was modified by the filler with concentration 30 wt. % and tested on mechanical properties i.e. the tensile strength, the elongation at break, the hardness and the impact strength. Results of the statistical analysis proved significant difference between measured values (p
Keywords: tensile strength; elongation at break; hardness; impact strength; SEM